Investigation of the role of Mrc1 in eukaryotic DNA replication - Timmerman, Adam, author; Schauer, Grant, advisor; Stasevich, Timothy, committee member; Santangelo, Thomas, committee member; Argueso, Juan Lucas, committee member (Colorado State University. Libraries, 2026)
DNA replication is a tightly regulated, complex process involving a multitude of protein complexes and cofactors. Living cells, across all domains of life, require efficient and accurate duplication of their genetic material prior to mitotic cellular division to proliferate. Because of the ubiquitousness of this process, replication-associated proteins are highly conserved among species. Replication stress, along with a host of other forms of cellular stress both, endogenous and exogenous, pose a substantial threat to this process due to the danger they pose to the integrity of a cell’s genome. Damage to the DNA, limitations on necessary components for replication, and conflicts between distinct protein machineries on the DNA template can all lead to replication stress. In eukaryotic cells, the S phase checkpoint, or replication checkpoint, has evolved to sense and mitigate replication stress and prevent mutations from arising and leading to disease. Two key components of this checkpoint in Saccharomyces cerevisiae are a pair of kinases: Mec1 (ATR in humans) and Rad53 (Chk1 in humans). Mec1 is recruited to stalled replication forks via recognition of extended tracts of RPA-bound single-stranded DNA, a result of helicase-polymerase uncoupling that is a hallmark of replication stress. From there, Mec1 activates Rad53, the effector kinase of the checkpoint that leads to downstream activation of numerous stress mitigation pathways including upregulating the expression of DNA repair mechanisms and stabilization of replication forks. Lying between these two kinases in the checkpoint is a mediator protein, Mrc1 (CLASPIN in humans). Initially identified for its role in mediating the replication checkpoint activation signal over two decades ago, Mrc1 has been extensively studied for its role not only in activation of the S phase checkpoint, but also in stimulation of replication rates, both in vivo and in vitro. Highly disordered and charged, Mrc1 has been difficult to characterize structurally; however, through various studies it is known that the mediator interacts with several components of the replication fork machinery, primarily CMG helicase and DNA Polymerase ε. These interactions are crucial for its functions during replication, but the mechanism underlying how these interactions relate to said functions are not clear. Here, we describe our understanding of the mechanism behind the role of Mrc1 in eukaryotic DNA replication. We determined that through its interactions with CMG and Polymerase ε, Mrc1 acts as a tether between the helicase and polymerase, coupling them both structurally and functionally. This tethering role is crucial to the balance between genomic integrity and replication efficiency, as interfering with the physical interactions lead to various phenotypes including increased sensitivity to replication stress-inducing drugs and amplified rates of mutagenesis. This and other findings presented in this dissertation provide insight to the mechanisms behind the growing number of identified functions of Mrc1 and the role this protein plays in ensuring the integrity of the genome and the efficiency of DNA replication.